A case of second lung cancer treated with bronchoplasty involving double-barrelled reconstruction after chemotherapy for squamous cell carcinoma at the bifurcation of left upper and lower lobe bronchus - Fujiwara, Toshiya; Kataoka, Kazuhiko; Senoo, Noritomo; Matsuura, Motoki; Nishikawa, Toshio (The Journal of the Japanese Association for Chest Surgery, 2010)
Regarding surgical treatment for second lung cancer, it is difficult to achieve radical cure while preserving the lung function. Case. A 57-year-old man. We had undergone right upper lobectomy and lymph node dissection for peripheral squamous cell carcinoma of the right S3; this tumor, of 21 mm in diameter, was diagnosed as pT1N0M0, stage I A. An endobronchial tumor was pointed out on chest CT six months postoperatively. It was diagnosed as central squamous cell carcinoma located at the bifurcation of the left upper and lower lobe bronchus and passed outside the bronchial wall based on bronchoscopic examination and biopsy. We thought that this tumor was a second lung cancer, but hesitated over the treatment method. To reduce the tumor size, we administered two courses of chemotherapy (carboplatin + weekly paclitaxel). The tumor size was reduced to 4 mm, and we performed sleeve resection of the bifurcation of the left upper and lower lobe bronchus with the left S6 and reconstructed the site through bronchoplasty with double-barrelled anastomosis. The final pathology was pT1N1M0, stage II A, but the patient has been recurrence-free for 5 years while undergoing regular follow-ups. When second lung cancer is of the central type, we should consider choosing the surgical procedure carefully based on the site of the tumor without compromising radical cure by combining chemotherapy and bronchoplasty with limited lung resection.